Correction: Synergistic effects of Zn and Pd species in TiO2 towards efficient photo-reduction of CO2 into CH4. (2nd July 2020) - Yu, Yanlong; Lan, Zijian; Guo, Limei; Wang, Enjun; Yao, Jianghong; Cao, Yaan
Abstract : Correction for 'Synergistic effects of Zn and Pd species in TiO2 towards efficient photo-reduction of CO2 into CH4 ' by Yanlong Yu et al., New J. Chem., 2018, 42, 483–488, DOI: ; 10.1039/C7NJ03305B .